Communication-based interventions to increase COVID-19 vaccine willingness and uptake: a systematic review with meta-analysis - Jessica Kaufman; Nicole Skoetz; Ina Monsef; Claire Iannizzi; Marike Andreas; Emma Bohndorf; Caroline Hirsch; Ana-Mihaela Zorger; Janine Brinkmann-Paulukat; Brigitte Bormann; Tina Lischetzki; Julia Neufeind; et al. (BMJ Open)
Objective This systematic review investigates the effectiveness of different communication strategies to increase COVID-19 vaccine uptake and willingness.Design Systematic review and meta-analysis of randomised controlled trials (RCTs), following recommendations from the Cochrane Handbook and reporting according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guideline.Data sources We searched the following databases until 27 July 2022: Cochrane COVID-19 Study Register, PsycINFO, CINAHL, Web of Science Core Collection and WHO COVID-19 Global literature.Eligibility criteria for study selection We included RCTs investigating, any population, communication-based interventions to increase COVID-19 vaccine uptake and comparing these with no intervention (with or without placebo), another communication strategy or another type of intervention.Methods Screening, data extraction and bias assessment, using the Cochrane ROB 1.0 tool, were conducted by two authors independently. We performed meta-analyses if studies were homogeneous using the Review Manager (RevMan 5) software, synthesised the remaining results narratively and assessed the certainty in the evidence using the Grading of Recommendations Assessment, Development, and Evaluation approach.Results We identified 49 studies reporting on the predefined four categories of communication interventions. Evidence from our meta-analyses shows that COVID-19 vaccine uptake may increase when education and information strategies are applied (risk ratio (RR) 1.23, 95% CI 1.17 to 1.28; high-certainty evidence) or social norms are communicated (RR 1.28, 95% CI 1.23 to 1.33; high-certainty evidence) compared with no intervention. The different communication strategies mostly have little to no impact on vaccine intention; however, there may be a slight increase in vaccine confidence when gain framing is applied compared with no intervention.Conclusion Overall, we found that education and information-based interventions or social norm-framing strategies are most effective compared with no intervention given. Our findings show that some of the investigated communication strategies might influence policy decision-making, and our results could be useful for future pandemics as well.PROSPERO registration number PROSPERO (CRD42021296618).